Peran Forum Pengurangan Resiko Bencana dalam Manajemen Bencana di Desa Sirnoboyo Kabupaten Pacitan - Mohamad Devic Pratama; Trisni Utami (Journal of Development and Social Change, 2022)
The role of the community to be independent in disaster situations is the main goal in disaster risk reduction. The existence of knowledge about disasters and the ability to save themselves makes people no longer dependent on groups engaged in disaster. In an effort to make the people of Sirnoboyo Village independent, the local village government in collaboration with local universities and BPBD formed a volunteer group for the Sirnoboyo Disaster Risk Reduction Forum (FPRB) to help create a disaster-resilient community. As a theoretical basis in this research, the theory of social capital is used which then includes three main concepts, namely networks, norms, and trust which then as a whole, the results of research related to the role of FPRB are seen with these three concepts. In this study, a qualitative descriptive method was used to answer the role of FPRB in disaster management and creating a disaster-resilient community. From this study it was found that in creating a disaster-resilient community, the FPRB carried out socialization, simulation, physical and non-physical mitigation efforts during pre-disaster. Then during the emergency response, the evacuation process and the construction of public kitchens became the main focus, and after the disaster, the FPRB assisted in the reconstruction of public facilities as well as the rehabilitation of the psychological condition of the community. FPRB also uses local wisdom such as the use of recitation culture, mutual cooperation, river festivals as a medium of socialization. Then also the use of traditional kentongan tools as a means of communication. From the efforts carried out by the Sirnoboyo FPRB, there are also supporting and inhibiting factors experienced by the Sirnoboyo FPRB both from the internal and external sides of the community itself.Keywords: Community, Disaster Management, Social Capital